Effectiveness of a Pre-Release Planning Program for HIV-Positive Offenders Exiting Georgia Prisons: A Qualitative Evaluation Approach - Willeford, Claire A (2010)
Background: Two-year nationwide prison recidivism rates stand at over 60%, and minorities and the poor are at greatest risk both of first-time incarceration and of offending repeatedly over time. Initiatives that may address prison inmates’ lack of resources and increase their success in their communities after release are now an important topic in the study of criminal justice policy. Over the course of the past two decades, the public health concern of HIV/AIDS has increasingly become a part of this discourse on re-entry, as the disease disproportionately affects minority communities both in and outside of prisons. Affected reentrants face not only the challenges associated with employment, education, housing, and other social infrastructure that impede their long-term re-entry into mainstream society, but must also navigate issues surrounding continuity of medical care and behavioral risk reduction. In 2009, Georgia State University received funding to conduct an evaluation of Georgia’s Pre-Release Planning Program (PRPP) for HIV-positive inmates, and conducted semi-structured interviews with 25 former inmates who had received services from PRPP. This thesis work attempts to assess the content of the interviews and the potential impact of such an evaluation on corrections policy, especially in light of other similar programs that have been funded nationwide. Methods: A literature review was conducted to provide information on state and Federal pre-release programs for HIV+ prisoners that have been funded since the 1990s. A qualitative analysis of the GSU interview transcripts, consisting of coding for major themes, was completed. The goal of the analysis was to determine what program components had been most beneficial to participants, and also what needs had gone unfulfilled. Results: Most participants (23/25) in receipt of pre-release planning services in Georgia felt that they had benefitted from the program. A majority (19/25) attended the appointments set up for them by the program coordinator. Respondents were generally satisfied with their medical care, though cases existed where respondents had been unable to access a stable provider or medication supply as planned. The greatest aid to participants from PRPP was in the area of medical care. Limitations were perceived in the areas of employment after release and the Department of Labor program to which PRPP referred participants, as well as housing to a lesser degree. Study participants acknowledged and appreciated the program coordinator’s hard work with the resources that she had, and recommended transitional housing and work programs as ideal resources to improve their situations. Almost all (22/23) expressed interest in a community mentoring program to aid their progress post-release. Conclusions: Literature showed a variety of education and prevention program models targeting HIV in prisons since the 1990s. The best program outcomes were associated with the longest period of intervention and the most intensive case management (Rhode Island), but further evaluation is needed, and funding for such programs is a real and consistent concern. When combined with the literature on previous and existing programs nationwide, the voices of these participants provide a good idea of what may be next for a successful pre-release program in Georgia. 1) Planning services should begin sooner before release—possibly at the time of admission to prison—and should provide a longer period of follow-up, in order to capitalize on the time available for intervention with this vulnerable population and to more effectively prevent recidivism. The addition of support staff for the Georgia PRPP may allow this to occur. 2) Provision or expansion of the community mentoring program proposed in Spaulding’s 2009 study and supported by participants in these interviews, providing for matching of mentors with mentees by family and ethnic background, may be an important way to improve health outcomes among this population while facing a dearth of funding. 3) Securing and advocating for additional funding for vocational, counseling, and medical support services available to the general prison population is crucial, in order to support opportunities for skills advancement and true corrections in life path among a historically deprived incarcerated population. A cost-effectiveness analysis by state officials is recommended in order to measure the true economic value of such programs—especially in contrast to the public burden of unchecked recidivism. 4) A change in the Georgia laws that severely restrict the civil rights of ex-felons—including the right to vote, to be considered for many job opportunities, to be admitted to certain professional schools, and to receive state or federal financial aid for secondary education—is essential if former inmates are to be realistically expected to succeed outside of prison